Online Marketing Strategy as A Solution to Increase the Sales Turnover of MSMEs Affected by COVID-19 OKU Regency - Rani Anwar; Titie Syahnaz Natalia; Angga Wibowo Gultom (Future Science)
This research aimed to see how significant the online marketing strategy is in increasing the sales turnover of micro, small and medium enterprises (MSMEs) in OKU Regency who were affected by COVID-19. The type of methodology used in this research was descriptive qualitative. The population in this research were micro, small, and medium enterprises (MSMEs) in OKU Regency who were affected by COVID-19. The sampling technique used in this research was 100 samples which were analyzed by purposive sampling. In collecting the data this research used in-depth interviews and documentation. In analyzing the data, this research used data reduction. This research analyzed two types of online strategy, free and paid online marketing strategy. The result of this study showed that online marketing strategy through social media whether free or paid contributed positively to the increment in sales turnover of micro, small and medium enterprises (MSMEs) in OKU Regency who were affected by COVID-19. The highest increment in turnover was a strategy that used paid social media features, there was a 165% increasement in sales turnover, while free online marketing strategy reached 16 % in increasing the sales turnover of micro, small and medium enterprises (MSMEs) in OKU Regency who were affected by COVID-19.